Investigating the Impact of E-Marketing Adoption on Marketing Success of Small Business Enterprises in Abia State, Nigeria - Njoku, Princewill Osinachi; Chiana, Cyril Anamelechi (Archives of Business Research, 2019)
This study was embarked upon to unearth the impact of E-Marketing adoption on marketing success of Small Business enterprises in Abia State, Nigeria. Primary and secondary sources of data were extensively employed. A sample size of 369 was determined using proportion method and was used for the study. The stated hypotheses were tested at 0.05 level of significance with simple regression in SPSS version 20. The paper revealed that e-marketing significantly impacts marketing performance and marketing effectiveness of SMEs in Aba, especially in the areas of profitability, market share, customer satisfaction, sales turnover, return on investment, reduction of sales cost, increased brand equity. The paper recommended that small business enterprises should imbibe the culture of training their staff periodically concerning e-marketing tools applications in their day to day activities. It further recommended that government should assist small business enterprises in the provision of basic amenities like steady power supply, internet facilities, conducive environment etc, so that they can compete favourably with their counterparts in the developed economies of the world, among others.